Research on the Teaching Mode of Master of Engineering Management based on CDIO - Tang, Genli; Liu, Qiuyan; Ding, Huajun (Scientific Journal of Technology, 2025)
Based on the concept of CDIO Engineering Education, this paper systematically discusses the problems existing in the current master's course teaching of engineering management specialty, and constructs the master's course teaching mode of Engineering Management Specialty Based on the concept of CDIO by analyzing the core characteristics of CDIO mode and the requirements of MEM course teaching, aiming to realize the organic unity of knowledge transfer and practical innovation, effectively improve the teaching effect of the master's course of engineering management specialty, and effectively respond to the talent demand change of the construction industry under the evolution trend of the era of knowledge economy.